Yes, And Yes. Issue 1 (July 2020) - Mieszkowski, Jan
Abstract : This essay argues that Derrida's exposition of the quasi-transcendental adverbiality of yes unfolds by marginalizing the quasi-transcendental conjunctionality of and . I begin by exploring the challenges of conceptualizing yes, a unique verbal element that resists determination as one word among others even as it appears to be a formative force that underwrites any and every word. The second part of the essay shows how Derrida downplays the role of and in the course of elaborating his theory of Joycean yes-laughter. I conclude by asking what it would mean to have the last word on a conjunction such as and, which by nature creates connections more than it brings sequences to a close. This question, I suggest, is crucial for understanding the powers and limits of language that claims to say 'yes' to language.